Perceptions of the Annual Review of Competence Progression (ARCP) in surgical training in the UK and Ireland: A prospective cross sectional questionnaire study. (July 2019) - Nally, D.M.; Elsey, E.; Humm, G.; Mohan, H.M.; ,
Abstract: Background: Surgical trainees in the UK and Ireland undergo rigorous formative and summative assessments throughout each placement, and appraisal at an Annual Review of Competence Progression (ARCP). The ARCP evaluates performance during each training year and determines progression to the next year of training. It is critical that the ARCP is a robust and fair process. The Association of Surgeons in Training (ASiT) sought to evaluate surgical trainees' experiences of the ARCP process in order to identify areas for improvement. Methods: An electronic survey was developed and distributed electronically to the trainee membership of ASiT in the UK and Republic of Ireland. A 57 point survey examined the specifics of one ARCP cycle as well as attitudes to the process in general. Quantitative analysis was performed, along with thematic analysis on the free-text comments. Results: 600 trainees from all deaneries, grades and specialities participated. The survey demonstrated difficulties in preparing for ARCP: insufficient notice (24%), inadequate communication (22%) and lack of engagement of seniors (30–39%). 47% considered the process and standards inconsistent. 82% of trainees considered a face-to-face ARCP advantageous. Such a meeting provided a means of raising concerns regarding training posts (29%), bullying (18%) and patient safety (17%) that would not otherwise have been reported in writing. During qualitative analysis, the following themes emerged: The conflict between potential value and real experience; concerns regarding the quality of assessment and the need for improvement (in process, individual performance and surgical training.) Conclusion: This survey demonstrates that trainees appreciate the potential educational value of the ARCP process. However, there is a gap between this potential and trainees experience. Particular concerns include inconsistency, the timing of decision-making and the need to retain a face-to-face meeting. This feedback from trainees can be used to improve the assessment process in relation to procedural developments at the national level and engagement of supervisors and trainers locally. These changes will ensure that the ARCP becomes a higher quality assessment and more constructive for training in future. Highlights: The ARCP process is under review by Health Education England. This ASIT study evaluated surgical trainees' experiences of ARCP. Difficulties experienced included inadequate notice (24%) and communication (22%) and poor engagement of seniors (30–39%). 47% considered the process and standards inconsistent. A face-to-face ARCP is advantageous to highlight issues that would not otherwise not be reported in writing. There was dissatisfaction with the true experience and the quality of assessment. The need for improvement was identified.